Mental Health Literacy among Secondary School Students Attending Government Schools in Kohalpur Municipality - Shrestha, Merina; Singh, Priyadarshini Shah; Rana, Dilsha; Jaiswal, Aakash (Journal of Nepalgunj Medical College, 2023)
Introduction: Mental Health Literacy is a broader concept under Health Literacy which enables a person to recognize mental disorders, seeks knowledge on prevention of mental diseases, ability to help others, increases use of available health services and enhances improved self-help strategies for better management of mental illness. Aims: To determine the sociodemographic factors that influence mental health literacy, assessment of knowledge, erroneous beliefs/stereotypes, help-seeking behaviours and self-help strategies associated with mental health. Methods: A descriptive cross-sectional survey was conducted among the selected secondary school students, by simple random technique from selected government schools in Kohalpur using the mental health questionnaire, (5-point Likert scale). Statistical analysis was done using SPSS 20 and levels of mental health literacy in various domains was calculated. Results: Among 420 participants, 53.33% were females and 46.67% males with mean age 15.12 years. The proximity to people with mental health problems was 13.1% and without was 86.9%. The Global Mental Health Literacy mean (3.67 with SD+/- 0.30) was taken as the reference point, the mean score above which is considered high and below it is low. Low levels of Knowledge (mean 3.64, SD+/- 0.43) and erroneous beliefs (mean 3.38, SD+/- 0.39) of mental health literacy were observed. Levels of self-help strategies (mean 3.96, SD+/- 0.703) was highest followed by help-seeking behaviours (mean 3.94, SD+/- 0.61). Conclusion: There are low levels of knowledge and high stereotypes/ erroneous beliefs in secondary school children studying in government schools. Programs aimed to increase knowledge and awareness on mental health and decrease stereotypes need to be implemented at schools.